MÚSICA, SEXUALIDAD, EDUCACIÓN. TRATAMIENTO DE LA DIVERSIDAD AFECTIVO-SEXUAL EN LA SERIE DE TELEVISIÓN GLEE - José A. Rodríguez-Quiles (European Scientific Journal, ESJ, 2015)
From the perspective of music education, I will here study the way in which the popular television series Glee deals with sexual diversity. I will base my analysis on queer theory and on the aesthetic of the performative, and methodologically I will choose the critical analysis of textual discourse as formulated by Fairclough (1995, 2001) to analyse the data and in turn examine the discoursive construction of LGBTI identities throughout the different seasons. We will see to what extent schools are important places for forming and regulating sexual identities and we will also understand the necessity of introducing global policies in order to fight LGBTI-phobia in these institutions. Instead of understanding school as a space that reflects the «natural distinctions», the series conceives of it as one of the territories where teenagers' sexual identities (among other things) are produced. Glee makes an effort to recognise and respect the diversity and singularity of pupils' experiencies, and all in an educational frame represented by the music classroom. We will thus understand the power of transformation which a performative music education can offer. In fact, it goes beyond mere expressivity and emotion until it becomes part of pupils' own lives and - no less important - it acts as an agent of change for social and political reflection.